Village governance in relation to coastal resource management in Fiji: a case study of Namada and Navukailagi villages - Tagivakatini, Serupepeli (2016)
The general aim of this research is to examine village governance structure and functions in the use, management and sustainability of coastal resources in Fiji. Traditional and contemporary systems of governance structures within the Fijian village setting play an integral role in decision-making for the well-being of every member in the community, and it is particularly important for matters relating to natural resource use. However, it is believed that poor governance is attributed to uncoordinated efforts of the dual governance system that continues to give rise to the many problems encountered in Fijian villages.